Brazil digital tool review for agroecological transitions - Heissler, Gustaco Haas; Lazzari, Helen Estima; Barbosa de Souza, Patricia; Costa, Aline Cassiano; Silveira, Roberta Flores; Dittmer, Kyle Michael; Costa, Ciniro (2023)
This document contains a review of digital resources relevant to climate-informed agroecological transitions for the beef cattle sector in Brazil. The purpose of the review was to catalog relevant digital resources for beef cattle production in Brazil and assess their role in inclusive knowledge development, with special attention to farmers’ co-creation of knowledge for on-the-ground practices. To this end, we identified existing digital tools in Brazil relevant to technical advisory and performance assessment for the beef cattle sector and reviewed their functions (i.e., the purpose of using a tool) against 87 indicators for exemplary features that could support socially inclusive climate-informed agroecological transitions.